2023
DOI: 10.53889/jpig.v3i1.149
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Poster Media on Senior High School Students' Communication Skills on Plant Tissue Concept

Abstract: One of the human needs is communication; communication is an activity of exchanging information verbally and non-verbally with one another to change behavior (Yanti, 2019). Learning media needed that can be used as a communication tool or intermediary that the sender will convey with the aim that the recipient can more easily receive the information conveyed (Megawati, 2017). One of the learning media used in the learning process is a poster. Poster learning media is said to be good if it includes legibility, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…(2021) implemented the biotechnology learning using pulau tunda's local potential, Sari et al (2022) conducted a systematic review on the implementation of bioinformatics learning in senior high school, Haryadi and Pujiastuti (2022) implemented STEM-PJBL model, Hendriyani et al (2023) used the project report through the STEM integrated project based learning model, and Widyastuti et al (2022) used discovery learning model through the aptitude treatment interaction (ATI). In the media learning, Baga et al (2021) used the comic media, Awaliyati et al (2021) developed the bacteria magz, Khastini et al (2022) developed the monopoly digestive media based on educational games, Wahyuni et al (2022b) developed the question card game, and Alya et al (2023) used the poster media, Syahfitri et al (2022) implemented the online learning using google classroom, Subagja et al (2022) conducted the student needs analysis of the scientific literacy oriented interactive multimedia, and Yuliani et al (2022) conducted a bibliometric analysis on mapping research on multimedia biology, Khastini et al (2023) implemented the estudent worksheets, and Ernawati and Sujatmika (2021) developed a worksheet based on a scientific approach. In the student learning outcomes, Fitriana et al (2022) analyzed the learning difficulties of class xii high school students and Yuliasari et al (2023) identified the students' misconceptions on the photosynthetic and plant respiration concepts using a two-tier diagnostic test.…”
Section: Introductionmentioning
confidence: 99%
“…(2021) implemented the biotechnology learning using pulau tunda's local potential, Sari et al (2022) conducted a systematic review on the implementation of bioinformatics learning in senior high school, Haryadi and Pujiastuti (2022) implemented STEM-PJBL model, Hendriyani et al (2023) used the project report through the STEM integrated project based learning model, and Widyastuti et al (2022) used discovery learning model through the aptitude treatment interaction (ATI). In the media learning, Baga et al (2021) used the comic media, Awaliyati et al (2021) developed the bacteria magz, Khastini et al (2022) developed the monopoly digestive media based on educational games, Wahyuni et al (2022b) developed the question card game, and Alya et al (2023) used the poster media, Syahfitri et al (2022) implemented the online learning using google classroom, Subagja et al (2022) conducted the student needs analysis of the scientific literacy oriented interactive multimedia, and Yuliani et al (2022) conducted a bibliometric analysis on mapping research on multimedia biology, Khastini et al (2023) implemented the estudent worksheets, and Ernawati and Sujatmika (2021) developed a worksheet based on a scientific approach. In the student learning outcomes, Fitriana et al (2022) analyzed the learning difficulties of class xii high school students and Yuliasari et al (2023) identified the students' misconceptions on the photosynthetic and plant respiration concepts using a two-tier diagnostic test.…”
Section: Introductionmentioning
confidence: 99%